2017
DOI: 10.18517/ijaseit.7.3.2216
|View full text |Cite
|
Sign up to set email alerts
|

Low Temperature Catalytic-Transfer Hydrogenation of Candlenut Oil

Abstract: Fatty acids containing more than one double bond (polyunsaturated fatty acids) indicated by high iodine value (more than 120 g I 2 /100 g oil) are prone either to oxidative degradation or thermal degradation leading to the appearance of undesirable compounds or to thermal oligo-/polymerization causing gum formation. Therefore, polyunsaturated bonds in the fatty acid chains should be hydrogenated into monounsaturated ones. The conventional method using hydrogen (direct hydrogenation) at relatively high temperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…It is important to note that observed increase in the progress of the reaction is marginal attributed to negative contribution from cuhioned collapse. In a recent work, Hadiah et al have clearly reported the beneficial effects to a large extent of increasing the temperature for the conventional approach of CTH of candlenut oil. It was reported that using a higher operating temperature reduced the required reaction time for a similar reduction in the iodine value, without observance of any optimum.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to note that observed increase in the progress of the reaction is marginal attributed to negative contribution from cuhioned collapse. In a recent work, Hadiah et al have clearly reported the beneficial effects to a large extent of increasing the temperature for the conventional approach of CTH of candlenut oil. It was reported that using a higher operating temperature reduced the required reaction time for a similar reduction in the iodine value, without observance of any optimum.…”
Section: Resultsmentioning
confidence: 99%
“…Typically higher water content leads to better contact between hydrogen donor and sunflower oil yielding higher exchange on the catalysts active sites and hence higher yields for the reaction expressed in terms of lower final acid value. Hadiah et al 16 reported that at the point when exchange hydrogenation is performed in a fluid emulsion with an acceptor, water is actively engaged in the reaction involving palladium as the active component of the catalyst. Also the use of higher quantities of water gives higher cavitational activity giving better progress of the reaction based on higher degree of intensification.…”
Section: Industrial and Engineering Chemistry Researchmentioning
confidence: 99%
“…Hydrogenation can be carried out via several methods, namely: conventional catalytic hydrogenation using high-pressure hydrogen gas; catalytic transfer hydrogenation with the help of hydrogen donor solution and solid catalyst [4]; and electrochemical hydrogenation. In this study, catalytic electrochemical (electrocatalytic) hydrogenation [5] was chosen for a number of reasons. This process does not utilize high-pressure hydrogen gas so that it eliminates high risk as well as high capital cost, which makes it more suitable for small-scale industrial applications.…”
Section: R + H 2 Rmentioning
confidence: 99%